Non-noble metal composite oxide catalyst as well as preparation method and application thereof
By using the non-precious metal composite oxide catalyst CexCuyO2, the redox capacity and active site density of the catalyst are improved by using Cu element modification, the problem of poor N2 selectivity of precious metal catalysts in the NH3-SCO process is solved, and high NH3 conversion rate and N2-selective non-precious metal catalysts, suitable for high and low temperature conditions.
Patent Information
- Application Number
- CN202410984312.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-07-22
AI Technical Summary
In the prior art, precious metal catalysts have problems such as poor N2 selectivity, high cost and insufficient thermal stability in the process of NH3 selective catalytic oxidation (NH3-SCO), and it is difficult to develop and take into account high NH3 conversion activity, high N2 selectivity and high stability. non-precious metal catalysts.
Using the non-precious metal composite oxide catalyst CexCuyO2, the redox capacity and surfactant site density are increased by Cu element modification, and a catalyst with high NH3 conversion and N2 selectivity is prepared. The specific method includes soluble cerium salt and copper salt. Hydrothermal reaction and calcination are carried out to form a catalyst for nanorod morphology.
The NH3 conversion rate is above 80% under 250°C, and the N2 selectivity is above 87% under 200°C. The NH3 conversion rate is still high at high temperature, with good low-temperature activity and stability, suitable for NH3 -SCO catalyst.
Smart Images

Figure CN119186572A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic materials, and in particular to a non-noble metal composite oxide catalyst and a preparation method and application thereof. Background Art
[0002] Ammonia (NH3) emissions have a serious impact on ecosystems. For example, NH3 can promote the formation of sulfates and secondary organosols in the atmosphere, contributing to haze pollution. Ammonia emissions originate from a variety of sources, primarily agriculture, industry, and transportation. NH3 emissions from motor vehicle exhaust are considered the primary source of NH3 in cities, particularly diesel exhaust using urea selective catalytic reduction (NH3-SCR) denitrification technology. NH3 slip is a common occurrence during the NH3-SCR process, necessitating the installation of an NH3 purification device at the end of the NH3-SCR purification system.
[0003] Currently, NH3 selective catalytic oxidation (NH3-SCO) technology is an effective and economical method for removing NH3. Its core is the efficient and stable NH3-SCO catalyst. NH3-SCO catalysts include precious metal catalysts, transition metal catalysts, composite oxide catalysts, and molecular sieve catalysts. Among them, precious metal catalysts are the most commonly used commercial NH3-SCO catalysts. However, precious metal catalysts have disadvantages such as poor N2 selectivity, high cost, and insufficient thermal stability.
[0004] CN117753409A discloses a precious metal silver-based NH3-SCO catalyst, its preparation method and application. Although the low-temperature activity is improved, the N2 selectivity is still poor; CN111068764A discloses a NH3-SCO catalyst Co-Cu / Beta for diesel vehicle exhaust. This molecular sieve catalyst is prepared by an impregnation method. Although it can improve the NH3 conversion activity and N2 selectivity to a certain extent, its structural stability is easily destroyed at high temperatures; CN109289889A discloses a precious metal Pt-loaded catalyst. Its precious metal Pt content is relatively high, the cost is high, and the selectivity for N2 is relatively poor. There are side reactions, and by-products such as NO, N2O, and NO2 are easily generated.
[0005] Therefore, how to develop a non-precious metal NH3-SCO catalyst that combines high NH3 conversion activity, high N2 selectivity and high stability has become an urgent problem to be solved. Summary of the Invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a non-precious metal composite oxide catalyst and its preparation method and use, wherein the non-precious metal composite oxide catalyst is Ce x Cu yO2 catalyst, wherein x+y=1, 0.05≤y≤0.55, using Cu element to promote the redox ability of the non-precious metal catalyst, the NH3 conversion rate of the catalyst at 250°C is above 80%, and the N2 selectivity at 200°C is above 87%. Further preferably, the NH3 conversion rate at 250°C is above 95%, and when the temperature is higher than 250°C, the NH3 conversion rate is still above 95%, and the non-precious metal composite oxide catalyst has high selectivity for N2 in the process of catalyzing NH3 conversion.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In the first aspect, the present invention provides a non-noble metal composite oxide catalyst, wherein the non-noble metal composite oxide catalyst is Ce x Cu y O2 catalyst, wherein x+y=1, 0.05≤y≤0.55, and y can be, for example, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or 0.55.
[0009] The present invention uses Cu as a modifying element. Cu increases oxygen vacancies, thus increasing catalytically active sites. Furthermore, Cu has high activity and can itself serve as an active site. Therefore, the presence of Cu increases the surface active site density of the catalyst, enhancing catalytic activity and effectively boosting the redox capacity of the non-precious metal catalyst.
[0010] The non-precious metal composite oxide catalyst of the present invention is used as an NH3-SCO catalyst, which can oxidize NH3 into N2 and H2O. The catalyst has an NH3 conversion rate of more than 80% at 250°C and an N2 selectivity of more than 87% at 200°C. More preferably, the NH3 conversion rate is more than 95% at 250°C. When the temperature is higher than 250°C, the NH3 conversion rate is still more than 95%, and has good low-temperature activity, N2 selectivity and stability.
[0011] Preferably, the Ce x Cu y The O2 catalyst has a nanorod morphology.
[0012] In a second aspect, the present invention further provides a method for preparing the non-noble metal composite oxide catalyst according to the first aspect, the preparation method comprising the following steps:
[0013] (1) uniformly mixing a soluble cerium salt, a soluble copper salt, and a solvent to obtain a mixed solution containing cerium and copper;
[0014] (2) uniformly mixing the precipitant solution with the mixed solution containing cerium and copper in step (1), performing a hydrothermal reaction, and performing solid-liquid separation to obtain a hydrothermal reaction product;
[0015] (3) calcining the hydrothermal reaction product of step (2) to obtain a non-noble metal composite oxide catalyst.
[0016] Preferably, the soluble cerium salt in step (1) includes any one of cerium nitrate hexahydrate, cerium carbonate or cerium oxalate, or a combination of at least two thereof.
[0017] Preferably, the soluble copper salt in step (1) includes any one of copper nitrate trihydrate, copper carbonate or copper oxalate, or a combination of at least two thereof.
[0018] Preferably, the molar ratio of Ce to Cu in the mixed solution containing cerium and copper in step (1) is x:y, wherein x+y=1, 0.05≤y≤0.55, and the molar ratio x:y can be, for example, 0.45:0.55, 0.5:0.5, 0.55:0.45, 0.6:0.4, 0.65:0.35, 0.7:0.3, 0.75:0.25, 0.8:0.2, 0.85:0.15, 0.9:0.1 or 0.95:0.05, etc.
[0019] Preferably, the solvent in step (1) comprises deionized water.
[0020] Preferably, the precipitant solution in step (2) comprises any one of sodium hydroxide aqueous solution, ammonia water or urea aqueous solution, or a combination of at least two thereof.
[0021] Preferably, the mixing method in step (2) includes: adding the precipitant solution to the mixed solution containing cerium and copper in step (1).
[0022] Preferably, the addition is accompanied by continuous stirring.
[0023] Preferably, the temperature of the hydrothermal reaction in step (2) is 80-120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C.
[0024] Preferably, the hydrothermal reaction time in step (2) is 8 to 16 hours, for example, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours.
[0025] Preferably, the solid-liquid separation in step (2) includes suction filtration.
[0026] Preferably, step (2) further includes washing and drying steps after the solid-liquid separation.
[0027] Preferably, the drying temperature is 80-120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C.
[0028] Preferably, the drying time is 12 to 24 hours, for example, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours.
[0029] Preferably, the calcination temperature in step (3) is 400-700°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C.
[0030] Preferably, the calcination time in step (3) is 2 to 6 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.
[0031] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0032] (1) uniformly mixing a soluble cerium salt, a soluble copper salt, and deionized water to obtain a mixed solution containing cerium and copper;
[0033] The soluble cerium salt includes any one or a combination of at least two of cerium nitrate hexahydrate, cerium carbonate, or cerium oxalate; the soluble copper salt includes any one or a combination of at least two of copper nitrate trihydrate, copper carbonate, or copper oxalate; the molar ratio of Ce to Cu in the mixed solution containing cerium and copper is x:y, wherein x+y=1, 0.05≤y≤0.55;
[0034] (2) adding the precipitant solution to the mixed solution containing cerium and copper in step (1) while continuously stirring the solution. After uniform mixing, the solution is hydrothermally reacted at 80 to 120° C. for 8 to 16 hours, filtered, and the product obtained by filtration is washed to neutrality, and dried at 80 to 120° C. for 12 to 24 hours to obtain a hydrothermal reaction product.
[0035] The precipitant solution includes any one of sodium hydroxide aqueous solution, ammonia water or urea aqueous solution or a combination of at least two thereof;
[0036] (3) calcining the hydrothermal reaction product of step (2) at 400-700° C. for 2-6 hours to obtain a non-noble metal composite oxide catalyst.
[0037] In a third aspect, the present invention further provides a use of a non-precious metal composite oxide catalyst, wherein the non-precious metal composite oxide catalyst described in the first aspect, or the non-precious metal composite oxide catalyst prepared by the preparation method described in the second aspect, after activity evaluation, is used as an NH3-SCO catalyst to oxidize NH3 to N2 and H2O.
[0038] Preferably, the temperature for activity evaluation is 150-300°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, etc.
[0039] Compared with the prior art, the present invention has at least the following beneficial effects:
[0040] (1) The non-noble metal composite oxide catalyst of the present invention is Ce x Cu y O2 catalyst, using Cu element to promote the redox ability of the non-precious metal catalyst, the catalyst has an NH3 conversion rate of more than 80% at 250°C, and an N2 selectivity of more than 87% at 200°C. Further preferably, the NH3 conversion rate is more than 95% at 250°C. When the temperature is higher than 250°C, the NH3 conversion rate is still more than 95%, and the catalyst has high selectivity for N2 in the process of catalyzing NH3 conversion and has high stability;
[0041] (2) The non-noble metal composite oxide catalyst of the present invention has a nanorod morphology, a simple preparation process, and is easy to industrially apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The Ce prepared in Example 1 of the present invention 0.7 Cu 0.3 Transmission electron microscopy image of the O2 catalyst;
[0043] Figure 2 is a transmission electron microscope image of the CeO2 catalyst prepared in Comparative Example 3 of the present invention;
[0044] Figure 3 This is a comparison chart of the NH3 conversion rates of the non-noble metal composite oxide catalysts prepared in Examples 1 to 5 of the present invention and the CeO2 catalyst prepared in Comparative Example 3;
[0045] Figure 4 2 is a comparison chart of the N2 selectivity of the non-noble metal composite oxide catalysts prepared in Examples 1 to 5 of the present invention and the CeO2 catalyst prepared in Comparative Example 3. DETAILED DESCRIPTION
[0046] The technical solution of the present invention will be further described below with reference to the accompanying drawings and through specific embodiments. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0047] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0048] Example 1
[0049] This embodiment provides a non-noble metal composite oxide catalyst and a preparation method thereof. The non-noble metal composite oxide catalyst is Ce 0.7 Cu 0.3 O2 catalyst, the preparation method comprises the following steps:
[0050] (1) 2.422 g of cerium nitrate hexahydrate and 0.578 g of copper nitrate trihydrate were added to 30 mL of deionized water and dissolved uniformly to obtain a mixed solution containing cerium and copper;
[0051] (2) 15 g of sodium hydroxide was dissolved in 50 mL of deionized water and dissolved uniformly, and then added to the mixed solution containing cerium and copper and stirred continuously. The mixed solution was then transferred to a reactor, hydroheated at 100° C. for 12 h, filtered, and the filtered product was washed to neutrality. After drying in an oven at 100° C. for 16 h, a hydrothermal reaction product was obtained.
[0052] (3) The hydrothermal reaction product was calcined in a muffle furnace at 550 °C for 4 h to obtain Ce 0.7 Cu 0.3 O2 catalyst.
[0053] Figure 1 The Ce prepared in this example is shown 0.7 Cu 0.3 Transmission electron microscope image of the O2 catalyst. It can be seen from the image that the catalyst as a whole has a nanorod morphology.
[0054] Example 2
[0055] This embodiment provides a non-noble metal composite oxide catalyst and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the non-noble metal composite oxide catalyst is Ce 0.6 Cu 0.4 O2 catalyst, in the preparation method, the mass of cerium nitrate hexahydrate in step (1) is 2.188 g, the mass of copper nitrate trihydrate is 0.812 g, and the remaining preparation methods and parameters are consistent with Example 1.
[0056] Example 3
[0057] This embodiment provides a non-noble metal composite oxide catalyst and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the non-noble metal composite oxide catalyst is Ce 0.5 Cu 0.5 O2 catalyst, in the preparation method, the mass of cerium nitrate hexahydrate in step (1) is 1.928g, the mass of copper nitrate trihydrate is 1.072g, and the rest of the preparation method and parameters are consistent with Example 1.
[0058] Example 4
[0059] This embodiment provides a non-noble metal composite oxide catalyst and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the non-noble metal composite oxide catalyst is Ce 0.8 Cu 0.2 O2 catalyst, in the preparation method, the mass of cerium nitrate hexahydrate in step (1) is 2.634 g, the mass of copper nitrate trihydrate is 0.366 g, and the remaining preparation methods and parameters are consistent with Example 1.
[0060] Example 5
[0061] This embodiment provides a non-noble metal composite oxide catalyst and a preparation method thereof. The difference between this embodiment and embodiment 1 is that the non-noble metal composite oxide catalyst is Ce 0.9 Cu 0.1 O2 catalyst, in the preparation method, the mass of cerium nitrate hexahydrate in step (1) is 2.825 g, the mass of copper nitrate trihydrate is 0.175 g, and the remaining preparation methods and parameters are consistent with Example 1.
[0062] Example 6
[0063] This embodiment provides a non-noble metal composite oxide catalyst and a preparation method thereof. The non-noble metal composite oxide catalyst is Ce 0.45 Cu 0.55 O2 catalyst, the preparation method comprises the following steps:
[0064] (1) 1.786 g of cerium nitrate hexahydrate and 1.214 g of copper nitrate trihydrate were added to 30 mL of deionized water and dissolved uniformly to obtain a mixed solution containing cerium and copper;
[0065] (2) 15 g of sodium hydroxide was dissolved in 50 mL of deionized water and dissolved uniformly, and then added to the mixed solution containing cerium and copper and stirred continuously. The mixed solution was then transferred to a reactor, hydroheated at 80° C. for 16 h, filtered, and the filtered product was washed to neutrality. After drying in an oven at 120° C. for 12 h, a hydrothermal reaction product was obtained.
[0066] (3) The hydrothermal reaction product was calcined in a muffle furnace at 400 °C for 6 h to obtain Ce 0.45 Cu 0.55 O2 catalyst.
[0067] Example 7
[0068] This embodiment provides a non-noble metal composite oxide catalyst and a preparation method thereof. The non-noble metal composite oxide catalyst is Ce 0.95 Cu 0.05 O2 catalyst, the preparation method comprises the following steps:
[0069] (1) 2.915 g of cerium nitrate hexahydrate and 0.085 g of copper nitrate trihydrate were added to 30 mL of deionized water and dissolved uniformly to obtain a mixed solution containing cerium and copper;
[0070] (2) 15 g of sodium hydroxide was dissolved in 50 mL of deionized water and dissolved uniformly, and then added to the mixed solution containing cerium and copper and stirred continuously. The mixed solution was then transferred to a reactor and hydroheated at 120° C. for 8 h, filtered, and the filtered product was washed to neutrality, and dried in an oven at 80° C. for 24 h to obtain a hydrothermal reaction product.
[0071] (3) The hydrothermal reaction product was calcined in a muffle furnace at 700 °C for 2 h to obtain Ce 0.95 Cu 0.05 O2 catalyst.
[0072] Example 8
[0073] This embodiment provides a non-precious metal composite oxide catalyst and a preparation method thereof. The difference between this embodiment and Example 1 is that in the preparation method, in step (2), the temperature of the hydrothermal reaction is 60° C., and the rest of the preparation method and parameters are consistent with Example 1.
[0074] Example 9
[0075] This embodiment provides a non-precious metal composite oxide catalyst and a preparation method thereof. The difference between this embodiment and Example 1 is that in the preparation method, in step (2), the temperature of the hydrothermal reaction is 140° C., and the remaining preparation methods and parameters are consistent with Example 1.
[0076] Example 10
[0077] This embodiment provides a non-precious metal composite oxide catalyst and a preparation method thereof. The difference between this embodiment and Example 1 is that in the preparation method, in step (3), the calcination temperature is 350°C, and the remaining preparation methods and parameters are consistent with Example 1.
[0078] Example 11
[0079] This embodiment provides a non-precious metal composite oxide catalyst and a preparation method thereof. The difference between this embodiment and Example 1 is that in the preparation method, in step (2), the calcination temperature is 750°C, and the remaining preparation methods and parameters are consistent with Example 1.
[0080] Comparative Example 1
[0081] This comparative example provides a non-noble metal composite oxide catalyst and a preparation method thereof. The difference between this comparative example and Example 1 is that the non-noble metal composite oxide catalyst is Ce 0.98 Cu 0.02 O2 catalyst, in the preparation method, the mass of cerium nitrate hexahydrate in step (1) is 2.966 g, the mass of copper nitrate trihydrate is 0.034 g, and the rest of the preparation method and parameters are consistent with Example 1.
[0082] Comparative Example 2
[0083] This comparative example provides a non-noble metal composite oxide catalyst and a preparation method thereof. The difference between this comparative example and Example 1 is that the non-noble metal composite oxide catalyst is Ce 0.4 Cu 0.6 O2 catalyst, in the preparation method, the mass of cerium nitrate hexahydrate in step (1) is 1.635 g, the mass of copper nitrate trihydrate is 1.365 g, and the rest of the preparation method and parameters are consistent with Example 1.
[0084] Comparative Example 3
[0085] This comparative example provides a CeO2 catalyst and a preparation method thereof. The difference between this comparative example and Example 1 is that, in the preparation method, only 3 g of cerium nitrate hexahydrate is added in step (1), and copper nitrate trihydrate is not added. The rest of the preparation method and parameters are consistent with Example 1.
[0086] Figure 2 The transmission electron microscope image of the CeO2 catalyst prepared in this comparative example is shown. As can be seen from the image, the CeO2 catalyst has a nanorod morphology.
[0087] Test Method
[0088] The Ce prepared in Examples 1 to 11 and Comparative Examples 1 to 2 x Cu yThe catalytic activity of the O2 catalyst and the CeO2 catalyst prepared in Comparative Example 3 was evaluated. The specific catalytic activity evaluation method is as follows: 100 mg of the catalyst was ground and sieved to obtain catalyst particles of 40-60 mesh size for testing; the test process was carried out in a fixed-bed reactor, and the simulated flue gas composition was: 500 ppm NH3, 10% O2, and N2 as the balance gas; the total flow rate of the simulated flue gas was 200 mL / min, and the reaction space velocity was 120,000 mL·h -1 ·g -1 The activity test results of the catalyst are shown in Table 1.
[0089] Figure 3 The NH3 conversion rate comparison diagram of the non-noble metal composite oxide catalysts prepared in Examples 1 to 5 and the CeO2 catalyst provided in Comparative Example 3 is shown. It can be seen from the figure that under the same reaction conditions, CeO2 x Cu y The low-temperature NH3 conversion activity of O2 catalysts is higher than that of CeO2 catalysts alone, indicating that the modification of Cu element can effectively promote the improvement of low-temperature activity of the catalyst. x Cu y The content of Cu element in O2 catalyst will also affect the catalytic performance of the obtained catalyst.
[0090] Figure 4 The N2 selectivity comparison diagram of the non-noble metal composite oxide catalysts prepared in Examples 1 to 5 and the CeO2 catalyst provided in Comparative Example 3 is shown. It can be seen from the figure that under the same reaction conditions, CeO2 x Cu y The N2 selectivity of O2 catalysts is higher than that of CeO2 catalysts alone, indicating that the modification of Cu element can effectively promote the improvement of low-temperature N2 selectivity of the catalyst. x Cu y The content of Cu element in the O2 catalyst will also affect the N2 selectivity of the obtained catalyst.
[0091] Table 1
[0092]
[0093] The test results show that:
[0094] (1) Ce provided by the present invention x Cu yThe O2 catalyst has excellent low-temperature NH3 conversion activity and good N2 selectivity. Combined with the preparation method provided by the present invention, the catalyst prepared has an NH3 conversion rate of more than 80% at 250°C and an N2 selectivity of more than 87% at 200°C. More preferably, the NH3 conversion rate at 250°C is more than 95%. When y is 0.3, Ce 0.7 Cu 0.3 The O2 catalyst has the best low-temperature NH3 conversion activity, with a conversion rate of up to 99.76% at 250°C and a N2 selectivity of 87.34% at 200°C.
[0095] (2) It can be seen from Examples 8 to 9 that if the temperature of the hydrothermal reaction is too high, the pore structure of the prepared catalyst will be destroyed, thereby reducing the specific surface area of the catalyst and causing a decrease in the NH3 conversion rate; if the temperature of the hydrothermal reaction is too low, the catalyst will not be fully crystallized, resulting in a significant decrease in the NH3 conversion rate and a decrease in the N2 selectivity;
[0096] (3) It can be seen from Examples 10 to 11 that if the calcination temperature is too high, the catalyst nanorod structure will be destroyed due to the high temperature, and the catalyst performance cannot be effectively improved, resulting in a significant decrease in NH3 conversion and N2 selectivity; if the calcination temperature is too low, the catalyst part will not form the target nanorod structure, resulting in a decrease in NH3 conversion;
[0097] (4) It can be seen from Example 1 and Comparative Examples 1-2 that when the value of y is too high or too low, it will affect Ce x Cu y O2 catalyst performance. If the y value is too high, that is, the Cu content is too high, it will block the surface active sites, not only will the performance of the catalyst not be further improved, but on the contrary will cause the catalyst NH3 conversion rate to decrease; if the y value is too low, that is, the Cu content is too low, the number of active sites will decrease, and it will not play the role of increasing oxygen vacancies, resulting in a decrease in the catalyst NH3 conversion rate and N2 selectivity;
[0098] (5) It can be seen from Example 1 and Comparative Example 3 that when CeO2 is used as a catalyst, it has few active sites and poor oxidation ability. The corresponding NH3 conversion rate at 250°C is only 1.16%, and there is no selectivity for N2 at 200°C.
[0099] In summary, the present invention utilizes the Cu element to promote the redox ability of the non-precious metal catalyst. The NH3 conversion rate of the catalyst at 250°C is above 80%, and the N2 selectivity at 200°C is above 87%. Further preferably, the NH3 conversion rate at 250°C is above 95%. When the temperature is higher than 250°C, the NH3 conversion rate is still above 95%. In addition, the non-precious metal composite oxide catalyst has high selectivity for N2 in the process of catalyzing NH3 conversion, which meets the current market application needs.
[0100] The applicant declares that the above is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the scope of protection and disclosure of the present invention.
Claims
1. A non-noble metal composite oxide catalyst, characterized in that: The non-noble metal composite oxide catalyst is Ce x Cu y O2 catalyst, wherein x+y=1, 0.05≤y≤0.
55.
2. The non-noble metal composite oxide catalyst according to claim 1, characterized in that: The Ce x Cu y The O2 catalyst is in the shape of nanorods.
3. A method for preparing a non-noble metal composite oxide catalyst according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) uniformly mixing a soluble cerium salt, a soluble copper salt and a solvent to obtain a mixed solution containing cerium and copper; (2) mixing the precipitant solution and the mixed solution containing cerium and copper in step (1) uniformly, performing a hydrothermal reaction, and performing solid-liquid separation to obtain a hydrothermal reaction product; (3) calcining the hydrothermal reaction product of step (2) to obtain a non-precious metal composite oxide catalyst.
4. The preparation method according to claim 3, characterized in that: The soluble cerium salt in step (1) includes any one of cerium nitrate hexahydrate, cerium carbonate or cerium oxalate, or a combination of at least two thereof; Preferably, the soluble copper salt in step (1) includes any one or a combination of at least two of copper nitrate trihydrate, copper carbonate or copper oxalate; Preferably, the molar ratio of Ce to Cu in the mixed solution containing cerium and copper in step (1) is x:y, wherein x+y=1, 0.05≤y≤0.55; Preferably, the solvent in step (1) comprises deionized water.
5. The preparation method according to claim 3 or 4, characterized in that: The precipitant solution in step (2) comprises any one of a sodium hydroxide aqueous solution, an ammonia solution or a urea aqueous solution, or a combination of at least two thereof; Preferably, the mixing method in step (2) includes: adding the precipitant solution to the mixed solution containing cerium and copper in step (1); Preferably, the adding is accompanied by continuous stirring.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The temperature of the hydrothermal reaction in step (2) is 80-120° C. Preferably, the hydrothermal reaction time in step (2) is 8 to 16 hours; Preferably, the solid-liquid separation in step (2) comprises suction filtration; Preferably, step (2) further includes washing and drying steps after the solid-liquid separation.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The calcination temperature in step (3) is 400-700° C. Preferably, the calcination time in step (3) is 2 to 6 hours.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing a soluble cerium salt, a soluble copper salt and deionized water uniformly to obtain a mixed solution containing cerium and copper; The soluble cerium salt includes any one of hexahydrated cerium nitrate, cerium carbonate or cerium oxalate or a combination of at least two thereof; the soluble copper salt includes any one of trihydrated copper nitrate, copper carbonate or copper oxalate or a combination of at least two thereof; the molar ratio of Ce to Cu in the mixed solution containing cerium and copper is x:y, wherein x+y=1, 0.05≤y≤0.55; (2) adding the precipitant solution to the mixed solution containing cerium and copper in step (1), stirring continuously during the adding process, and after mixing evenly, hydrothermally reacting at 80 to 120° C. for 8 to 16 hours, filtering, washing the filtered product to neutrality, and drying at 80 to 120° C. for 12 to 24 hours to obtain a hydrothermal reaction product; The precipitant solution includes any one of a sodium hydroxide aqueous solution, an ammonia solution or a urea aqueous solution, or a combination of at least two thereof; (3) calcining the hydrothermal reaction product of step (2) at 400-700° C. for 2-6 hours to obtain a non-precious metal composite oxide catalyst.
9. Use of a non-precious metal composite oxide catalyst, characterized in that: The non-precious metal composite oxide catalyst according to claim 1 or 2, or the non-precious metal composite oxide catalyst prepared by the preparation method according to any one of claims 3 to 8, is used as an NH3-SCO catalyst to oxidize NH3 into N2 and H2O after activity evaluation.
10. The use according to claim 9, characterized in that The temperature for the activity evaluation is 150-300°C.
Citation Information
Patent Citations
Pt-based ammoxidation catalyst modified with nitrogen-containing organic matter electron promoter, and preparation method thereof
CN109289889A
NH3-SCO catalyst for diesel vehicle tail gas and preparation method of NH3-SCO catalyst
CN111068764A
Silver-based NH3-SCO catalyst and preparation method and application thereof
CN117753409A
CeO2 / CuO catalyst for CO preferential oxidation and hydro-thermal synthesis method thereof
CN102895977A
Ce-BASED COMPOSITE OXIDE CATALYST, PREPARATION METHOD AND APPLICATION THEREOF
US20130202513A1